Пластика з трипільського поселення-гіганта Тальянки (комплекс "Сім’я гончаря 1”, розкопки 2011 — 2017 рр.) - Овчинников, Е.В. (Археологія і давня історія України, 2021)
Стаття присвячена аналізу предметів пластики, знайдених на території житлово-виробничого
комплексу «Сім’я гончаря 1» з трипільського поселення Тальянки, і їх планіграфії. During 2011—2017 Trypillian expedition of the Institute
of Archaeology of NASU carried out research
of the residential-industrial complex «Ceramist’s
Family 1» on the trypillian settlement-giant Talyanki
(3800 BC, Tomashivskaia locally-chronological version
of the culture). This complex was located in the
western part of the northern sector of the settlement.
Its boundaries determined by gaps in the built-up of a
single line of the houses. As a separate structure of the
settlement, this complex consisted from five houses,
three kilns, a production pit, consisting of several depressions,
and two small pits.
This article is devoted to analysis of ceramic items
that are usually associated with ritual and ceremonial
activities and foundon the territory of the designated
complex, primarily their planigraphic distribution.
The collection consists of 67 items and includes 17 anthropomorphic
and 9 zoomorphic figurines, 2 models of
dwellings, 18 models of sledges, 4 models of vessels, 6
small geometric objects (balls, cones, chips), 3 ceramic
ornaments and 8 small relief pieces that are not part
of ceramic vessels. Most of the items found in the pit
(46 items), a smaller number of them are associated
with the residential sector of the complex (20 items)
and only half of them (12 items) originate directly from
houses, the rest are distributed in the adjacent territory
within a radius of 1—4 m from residential buildings.
Only one item found in the kiln «D».
The vast majority of «terracotta» items are fragmented.
Its disposal, like the ceramic dishes, went the
same way — the debris taken out of the houses. Most
of them fell into the pits; a smaller part of the ceramic
broken used as a building material for the construction
of kilns. Overall, the ratio of vessels fragments
and fragments of «terracotta» items at different objects
of the complex is close. Therefore, for 20 units of «terracotta
» items found in houses and the adjacent territory,
there are about 11 thousand ceramic fragments
of vessels. Forty-six of «terracotta» items from the
big pit oppose for about 13 thousand of ceramic fragments
of dishes. Only one fragment of the sledge model
comes directly from the kiln construction. Unique «terracotta
» items, high quality wares, did not lose their
importance, probably even after the breakdown. They
either put in special places or disposed of in a special
way. Thus, entire models of sledges was found on the
podium in house 47, and a model of a uniquely shaped
found in the lowest ash layer in one of the depressions
of the large pit near the kiln «D». In rare cases, anthropomorphic
and zoomorphic figurines founded in the
deepest parts of the pit.
The difference in the technical and technological
characteristics of various «terracotta» items may indicate
that the need to make sculptures sometimes arose
spontaneously and was far from always associated
with the specialized work of the kiln. We assume the
likelihood of a wide range of participants in the «terracotta
» making process, in which, in addition to potters,
there could be «non-professionals» — children, apprentice,
etc.